CETRA 『Target』誌20周年記念国際会議 The Known Unknowns of Translation Studies の報告 - TAKEDA, Kayoko (Interpreting and Translation Studies: The Journal of the Japan Association for Interpreting and Translation Studies, 2009)
On the occasion of the 20th anniversary of CETRA and Target, an international conference titled The Known Unknowns of Translation Studies was held at Katholieke Universiteit Leuven in Belgium on August 28-29, 2009. This conference review presents a summary of the talks given by the keynote speakers (past CETRA professors) and brief comments by the author.